DISCIPLINE OF GREEK STUDENTS IN RELATION TO GENDER, INTEREST IN PHYSICAL EDUCATION LESSON AND SPORT ACTIVITY - Panagiotis Ioannou; Panteleimon Bakirtzoglou (SportLogia, 2011)
The purpose of this study was to compare the differences between different groups (student’s gender, type of school, interest in physical education and sport activity outside school hours), based on the student’s disciplined/undisciplined behavior in the physical education class. Sample consisted of 565 secondary education students aged between 15 and 16, in the Region of Athens (Greece). Participants completed the following scales: Reasons for Discipline Scale (RDS) and Strategies to Sustain Discipline Scale (SSDS). Results showed that female students were more disciplined and perceived more intrinsic reasons in their teachers for maintaining discipline than boys, who demonstrated more undisciplined behavior and perceived more reasons of indifference or introjection in their teachers to maintaining discipline. On the other hand, students that liked physical education and did sport were more disciplined and perceived more intrinsic reasons in their teachers for maintaining discipline.